LEGAL PROTECTION OF INDIGENOUS PEOPLE'S RIGHTS IN THE UTILIZATION OF NATURAL RESOURCES - Prasetia, Ristiantika (Communale Journal, 2023)
This journal thoroughly explores problems and potential solutions related to the legal protection of indigenous peoples' rights in using local natural resources in Indonesia by basing the analysis on a multidisciplinary perspective, which includes legal, cultural, and socio-economic impacts. The juridical-normative approach is used to evaluate the legal framework governing the rights of indigenous peoples, while the empirical approach involves concrete case studies to understand its practical implementation. The findings highlight the gap between existing legal provisions and the realities on the ground, identifying current challenges such as conflicts of interest, industrialization, and globalization. An in-depth analysis of possible solutions, including policy improvements and strengthening legal mechanisms, provides holistic insights into improving the protection of indigenous peoples' rights. It is hoped that this journal can be an essential contribution to the development of more inclusive and sustainable policies, as well as increase understanding of the urgency of legal protection of indigenous peoples' rights in the context of local natural resource utilization.